Putting Attention on the Spot in Coaching: Shifting to an External Focus of Attention With Imagery Techniques to Improve Basketball Free-Throw Shooting Performance - Milley, Kyle R.; Ouellette, Gene P. (Frontiers in Psychology, 2021)
Attentional focus is an area that has garnered considerable attention in the sport psychology and motor performance literature. This is unsurprising given that attentional focus has been directly linked to performance outcomes and is susceptible to coaching input. While research has amassed supporting benefits of an external focus of attention (EFA) on motor performance using verbal instruction, other studies have challenged the notion that an EFA is necessarily more beneficial than an internal focus of attention (IFA) for sport related performance. Further, it is unclear what type of instructions may serve to direct an athlete to an EFA, and in particular, if coaching can utilize imagery to orient an athlete towards an EFA. In the present exploratory study, we evaluate the effectiveness of instruction to improve free throw shooting performance with an emphasis on an EFA brought about by implementing techniques borrowed from the imagery literature. This was tested relative to an alternate approach with an IFA induced through an emphasis on technique, devised to more closely resemble input typical of coach-to-athlete instruction. Twenty-five male and female university basketball players completed both conditions in a fully counterbalanced within-subject design. Results confirmed that participants in the EFA imagery condition had greater shooting accuracy than in the IFA technique condition. The study provides initial evidence that EFA coaching can borrow from imagery techniques, though future research should elucidate the underlying mechanisms of the effect.